POTENSI WISATA ALAM DI KAWASAN CAGAR ALAM GUNUNG DAKO KABUPATEN TOLI TOLI - Asril, .; Toknok, Bau; Sustri, . (Jurnal Warta Rimba, 2018)
Forest area in the village of Kinopasan is a forest area of Mount Dako Nature Reserve managed by Natural Resources Conservation Center (BKSDA) Central Sulawesi, the area also has a wealth of flora and fauna are very diverse that can support the development of natural attractions. The purpose of this study is to find out the feasibility of natural tourism potential in the village of Kinopasan Galang District Toli Toli regency as a tourist destination. This research use survey method, documentation and interview, while Data analysis used is Guideline (ADO-ODTWA) Director General PHKA Year 2003 according to value which have been determined for each criterion. The result of the research indicates that the natural potency in the forest area of Kinopasan Village, Toli Toli regency, is suitable to be a tourist destination with feasibility level, based on eligibility criteria of each element / sub criteria such as attractiveness, accessibility, akomondasi and supporting facilities and infrastructures, amounting to 86.45% of the total value assessment element / sub criteria which means the village is worthy of being used as a tourist destination.